Antioxidant Activity and Organoleptic Value of Ancak Buffalo Milk Typical of LombokIDAN DAN NILAI ORGANOLEPTIK ANCAK SUSU KERBAU KHAS LOMBOK - Handini, Denek Bini Dwi; Wulandani, Baiq Rani Dwi; Kisworo, Joko (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Ancak is a traditional food from Nusa Tenggara which is made with buffalo milk raw materials through a heating process with the addition of salt and vidarius sap (Calotropis gigantea). There has been no research on the antioxidant activity and organoleptic value of Lombok's typical buffalo milk ancak while the same research has been carried out on similar traditional dairy products such as curd and dangke. The antioxidant analysis method used in this study was based on the IC50 (Inhibition Concentration 50 value) value. IC50 is obtained by inserting the absorbance of the sample based on the spectrophotometer into the regression equation y=ax + b. Different levels of biduri sap supplementation showed strong antioxidant activity in ancak as evidenced by the decrease in IC50 value. The lowest IC50 value was found in the administration of biduri sap with the highest dose (1 ml/lt). In the control, it showed an IC50 value of 51.95 ppm, in the addition of 0.6 mL/lt of biduri sap it produced an IC50 value of 30.15 ppm, in the addition of 0.8 mL/lt it showed 31.02 ppm and in the addition of 1 mL/lt it showed an IC50 of 5.78 ppm. The results of the organoleptic test showed that the application of biduri sap had a significant effect on the organoleptic value of ancak. Based on the hedonic test, ancak without treatment is preferred over ancak with treatment. The scores of ancak acceptance were control (3.00), treatment 2 (2.68), treatment 3 (2.61) and treatment 1 (2.54).